Hemorrhagik Sindrome in Chronik Diffuze Liver Diseases - Kurbonova Z.Ch; Babajanova Sh.A; Filiz Maraslioglu; Sayfutdinova Z.A; Shodiyeva G.E (Genius Journals, 2023)
The main signs of hemorrhagic syndrome in chronic hepatitis and liver cirrhosis with viral etiology were divided into the nosebleeds in 32.76%, gums bleeding in 27.59%, skin petechia in 25.0%, hemorrhoidal bleeding in 19.83%, bleeding from varicose veins of the esophagus in 18.96%, menorrhage in 17.24% and bleeding from the gastrointestinal tract in 16.38% of patients. Hemorrhagic syndrome was expressed in cirrhosis of the liver HBV and HBV + HDV etiology 57.14% and 62.50%, respectively, to a lesser extent with cirrhosis of the liver HCV etiology 34.78%, but in liver cirrhosis of non-viral etiology hemorrhagic syndrome was detected in 25% of cases. In chronic viral hepatitis HBV and HCV etiology hemorrhagic syndrome was 11.76% and 5.26%, respectively, which indicated a lesser violation of the hemostasis system than in liver cirrhosis with viral etiology. As soon as there is a pronounced hemorrhagic syndrome in liver cirrhosis with viral etiology, a detailed study of coagulation and vascular platelet hemostasis is required to prevent and treat bleeding syndrome
Keywords: hemorrhagic syndrome; liver cirrhosis; chronic hepatitis